The Legacy of New Criticism (Journal of Teaching and Research in English Literature, 2012)
Though literary criticism is as old as literature itself, it was only in the twentieth century its manifestation was observable in diverse forms. Among these the most noteworthy movement that effected a total transformation of the discipline of English Studies goes by the name of New Criticism. Its origin and growth could be seen running parallel to Modernism in the arts. By mid 1930s or so, it got entrenched in the universities in the English speaking world. And in the post-war years, theories about the language of poetry—poetry as ontology, for instance—favouring close textual analysis helped in strengthening its claims, buttressed by learned journals. As matters stand now in the second decade of the twenty-first century, its assumptions stand discredited, outdated. For example, Structuralism opposes its focus on individual works in isolation. Deconstruction’s emphasis on the elusiveness of language which undermines itself is in direct contrast to the New critical theory on the primacy of language. New Historicism/Cultural Materialism too, with its faith in the principle of negotiation and appropriation among parallel texts does not accommodate its view. The major charges levelled against New Criticism are: it shows little concern with the social function of literature; it is unhistorical, since it isolates a work from its origins and context, concerning itself with only the two elements which constitute a work—the subject, and the words in which it is expressed, rejecting any continuity with the experiences of its creator and its reader; and, its method of reasoning deductive..